ChemInform Abstract: Green and Size‐Controllable Synthesis of Photoluminescent Carbon Nanoparticles from Waste Plastic Bags. Issue 4 (January 2015) - Hu, Yaoping; Yang, Jing; Tian, Jiangwei; Jia, Li; Yu, Jun‐Sheng
Abstract Photoluminescent carbon nanoparticles (CNP) are prepared by size‐controllable hydrothermal treatment (autoclave, 180 °C, 12 h) of various waste plastic bags in highly diluted H2O2 solutions (≤5.0 wt%) involving oxidative degradation, carbonization, and passivation followed by dialysis (molecular weight cut‐off: 1, 000 Da) and freeze‐drying of the obtained solution.